Analisis Efektivitas Biaya Penggunan Obat Antidiabetes pada Pasien Diabetes Melitus Tipe 2 di Instalasi Rawat Inap Rumah Sakit TK. II Dr. R. Hardjanto Balikpapan - Suci Indah Rachmayani; Eka Kumala Retno; Warantia Citta Citti Putri (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Type 2 Diabetes Mellitus is a chronic disease with an increasing prevalence and requires long-term therapy, resulting in a significant economic burden on healthcare systems. This study aimed to analyze the cost-effectiveness of antidiabetic drug use among Type 2 Diabetes Mellitus patients in the inpatient unit of Dr. R. Hardjanto Hospital, Balikpapan. This research employed an observational analytic design with a cross-sectional approach and retrospective data collection from medical records and administrative data for the period January–December 2023. A total of 54 patients who met the inclusion criteria were included as study samples. Therapeutic effectiveness was assessed based on the achievement of random blood glucose levels ≤200 mg/dL, while the analysis focused on direct medical costs. Cost-effectiveness was evaluated using the Average Cost-Effectiveness Ratio (ACER) and Incremental Cost-Effectiveness Ratio (ICER). The results showed that Metformin–Apidra therapy achieved higher clinical effectiveness (92%) with an average cost of IDR 3,636,721 and an ACER value of IDR 39,529. Meanwhile, Glimepiride–Sansulin therapy demonstrated 81% effectiveness with a lower average cost of IDR 2,519,259 and an ACER value of IDR 31,101. The ICER value of IDR 10,158 indicates the additional cost required to achieve a 1% increase in effectiveness. In conclusion, Metformin–Apidra therapy is more clinically effective, whereas Glimepiride–Sansulin therapy is more cost-effective economically.